Price reaction of ethically screened stocks: a study of the Dow Jones Islamic Market World Index - Mazouz, Khelifa; Mohamed, Abdulkadir; Saadouni, Brahim (Springer, 2016)
This paper investigates the short-term effects on the price of the ethically screened stocks of the Dow Jones Islamic Market World Index (DJIMWI) quarterly revisions. Using a sample of 8250 stocks from May 1999 through June 2012, we find a significant price reaction of the ethically screened stocks following additions and deletions. The results show that additions (deletions) from emerging stock markets tend to experience a greater and significantly positive (negative) price response than additions (deletions) from the developed markets. Further tests reveal that the price reactions following DJIMWI revisions are likely to be driven by shifts in investor sentiment rather than changes in firm fundamentals.
Keywords: Ethically screened stocks; Additions and Deletions; Dow Jones Islamic Market World Index; Emerging and developed markets; Investor sentiment